Risk Identification and Safety Assessment in Kemuning Sky Hills Tourism Area - Yasmin Zulfa Agustin Alfiyah Hariyanto; Bambang Suhardi; Rahmaniyah Dwi Astuti; Irwan Iftadi; I Wayan Suletra; Ade Aisyah Arifna Putri; Eko Liquiddanu (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret (UNS), 2026)
Kemuning Sky Hills is a natural tourist attraction in Karanganyar Regency that offers various extreme rides, including a glass bridge, a sky swing, a flying chair, and a flying bicycle. Although it attracts tourists, the safety risks associated with these rides have not been optimally managed. This study aims to assess safety risks using the Hazard Identification, Risk Assessment, and Determination of Control (HIRADC) and provide a deeper understanding of the importance of safety risk analysis in extreme tourism destinations. The risk assessment is based on the Australian Standard HB 205-2004 reference. Data were collected through direct observation, interviews with officers and visitors, and field documentation. The results showed that several potential hazards fall into the High Risk to Extreme Risk categories. There are 10 risks in the High Risk category and 4 risks in the Extreme Risk category. The most extreme risks identified include overloading due to visitor density, gaps in the fence on the Glass Bridge, broken ropes on the Sky Swing, and the threat of landslides in the tourist area. Proposed controls include installing safety nets, rope guides, and warning signs, establishing a structured maintenance schedule, and providing education. This study concludes that safety management at Kemuning Sky Hills should be strengthened by implementing an integrated, structured safety management system that includes standardized operational procedures, routine risk assessments, clear emergency response mechanisms, and continuous staff training to ensure a consistently safe and sustainable tourist environment.